Pelatihan Aplikasi Mendeley untuk Peningkatan Kualitas Penulisan Karya Ilmiah Mahasiswa - Aisyah, Nur; Windasari, Ihsanul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Scientific writing is a fundamental competency that must be mastered by students as part of the learning process and the development of knowledge. One of the major challenges in academic writing is the management of references, including the preparation of citations and bibliographies in accordance with academic standards. At the University of Al-Qolam Malang, many students still encounter difficulties in effectively utilizing reference management software, particularly Mendeley. To address this issue, a community service program was conducted in the form of Mendeley training for students, using a hands-on practice approach supported by active facilitation. The results of the activity indicate an improvement in students' digital literacy related to reference management, the ability to generate citations and bibliographies automatically, and an increased awareness of academic ethics. Furthermore, the program encouraged the emergence of an initiative to form a Mendeley user community as a sustainability effort. Recommendations include integrating Mendeley training into the curriculum, providing digital modules, offering advanced training, and strengthening institutional support through collaboration with strategic campus units. Therefore, this training contributes to enhancing the quality of students’ academic writing and fostering a technology-based academic culture within the University of Al-Qolam Malang.